Spatial distribution, territoriality and sound production by tropical cryptic butterflies (Hamadryas, Lepidoptera: Nymphalidae): implications for the ''industrial melanism" debate - Monge-Nájera, Julián; Hernández, Francisco; González, María Isabel; Soley, Javier; Araya, José; Zolla, Stefano (Revista de Biología Tropical, 1998)
Neotropical buttert1ies of the genus Hamadryas, noted b y the emission of sound, spend much lime perching on trees and are believed 10 be cryptically pattemed and colored with respecI lo Iree trunks and branches ¡hey use as perching siles, bul ¡he subject had not been studied previously. This paper describes spatial distribution, territoriality ¡¡nd sound production in five species, under natural conditions: Hamadryas amphinome (Lucas, 1 853), H. februa (Godart, 1 824), H. feronia (Fruhstorfer, 1 916), H. glaucollome (Bates, 1 864) and H. guatemalena (Bates, ! 864). Tree characteristics and use by bunerflies were recorded under natural conditions in open habitats (grassland thinly eovered with trees) in Costa Riea and Panama, avoidíng the problems thal affected previous natural selection studies in Biston betularía (the "industrial melanism" moth). Males perched on the trees and used Ihem as courting territories. The butterflies perched more oflen on sorne individual trees, and dia no! use olhers. The general Iree bark ("background") color tended to match wing coloration, while presence of food, position of teees along flight routes, Iree size, bark texture, and lichen cover were nol associated with the frequency of perching on ¡he trees. Mosl individuals Ihat perched in the study sites were males . Species differed in perching height and populations of H. februa perched al the same heights in both countries; H. leronia moves 10 higher perches near day's end. The relative use of branches and trunks is nOI related lO the time of day bul reflects the typical perehing height of each species. The northem side of trees is less used and cardinal side distribution is independent of time of day. Perches exposed to direct sunlight are less used in hot day s . Al! species perch with the head downwards. Perching males frequently fly towards orher Hamadryas as well as towards tethel'ed cardboard models. Trees with experimentally removed males were taken by newcomers 32 times more ofien Ihan trees with resident males. Eaeh marked H. feronia male was seen perching on 1 -4 trees daily, without difference between seasons, and each tree used had a minimum daily mean of 1 .5 perching butterflies. Mos! H. leronia interaetions occur from 1 3:00through 1 5 :00 hours and are more fl'equent in tbe fmny season. At night males share perches. Sound emission was studied by using non-destructive experimental methods (N=85 8 ) and with a scanníng electron microscope. B oth sexes emit sound and the sound apparatus , located in the forewing, is percussive, no! stridulatory. At the end of the upward wingstroke, the wings are c1apped and modified [-m 1-2 veins meet al a speed of approximately 1 42 0 mm/s, producing the characteristic c1ícks . Wingbeat frequency of free-fiying individnals is 20-29 Hz. There is sorne wing deformatíon during movement. Clicks lasl a mean of 1 .3 8 ms with mean intervals of 43 .74 ms and the component frequencies concentrate around 2.4 kHz, matching Hamadryas heariug capacity and being appropriate for the acoustic conditions of habitat. The swollen Se vein is present exclusively in Hamadryas; has a serpentine strueture inside and probably acts as resonance box. Growth of the sound apparatus may be checked by its effect on flight capacity, physiological costs and ecological reasons. AlI Hamadryas have a membrane, shaped as an elongated cupola, in the costal cell, that acts as ear. A second and smaller ear has fOUT chambers and may detect predatory bats when the insects are perching at nighl. Field observations showed that Hamadryas spp. emit audible c1icks when approached by potential predators, to defend territories from other Hamadryas and in at least one speeies also during eourtship. Severe wing damage, eommon in wild Hamadryas, almost never affects the sectíon with the sound mechanism. A review of Ihe Iiterature shows Ihat more than 50 species of lepidopterans ( 1 1 families) emit sound audible lo humans and suggests that sound mechanisms evolved several times. In general, lepidopteran sound is used basically as a warning to predators and for intraspecific communication.